1967
DOI: 10.1037/h0024805
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic mechanisms for sexual, aggressive, and other motivational behaviors in the opossum, Didelphis virginiana.

Abstract: Male mating behavior, biting attack, defensive threat, eating, grooming, yawning, investigating, and escape-like activity were produced by electrical stimulation of differentiated zones in hypothalamus and preoptic area of oppossums. Close anatomical correspondence with similar mechanisms in higher species suggested considerable phylogenetic continuity from early mammalian levels. Responses involving environmental goals were not performed without the objects, indicating that they were facilitated rather than d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
1
1

Year Published

1969
1969
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(71 citation statements)
references
References 22 publications
6
63
1
1
Order By: Relevance
“…A ventral extension of the system similar to that in the chick can be seen just in front of the mamillary area. This is further confirmed in the opossum [Roberts et al, 1967] where a defensive threat area was found to centre on nu. ventromedialis.…”
Section: Discussionsupporting
confidence: 64%
“…A ventral extension of the system similar to that in the chick can be seen just in front of the mamillary area. This is further confirmed in the opossum [Roberts et al, 1967] where a defensive threat area was found to centre on nu. ventromedialis.…”
Section: Discussionsupporting
confidence: 64%
“…Lesion and electrical stimulation studies in rodents, cats, dogs, and monkeys have revealed several important areas in the forebrain that play a role in male reproductive behavior, such as the neocortex (for review see Meisel and Sachs, 1994), the main and accessory olfactory systems in rats but not in other species (Giantonia et al, 1970;Aronson and Cooper, 1974;Hart and Haugen, 1972;Goldfoot et al, 1978), the corticomedial nucleus of the amygdala (Giantonia et al, 1970; for review see Meisel and Sachs, 1994), the caudal medial preoptic area/anterior hypothalamus (e.g., Larsson and Heimer, 1964;Heimer and Larsson, 1966;Roberts et al, 1967;Malsbury, 1971;Hart et al, 1973;Van de Poll and Van Dis, 1979;Hansen et al, 1982;Hart and Leedy, 1983; for review see Meisel and Sachs, 1994).…”
Section: Functional Implicationsmentioning
confidence: 98%
“…Morgane & Kosman, 1960) and primate (e.g., Hamilton & Brobeck, 1964a). In the same vein, electrical stimulation of the lateral region has been found to induce eating in aIl species studied including the rodent (e.g., Miller, 1957), marsupial (e.g., Roberts, Steinberg & Means, 1967), carnivore (e.g., Anand & Dua, 1955), ruminant (e.g., Larsson, 1954), and primate (e.g., Robinson & Mishkin, 1962). …”
Section: The Ro1e Of the Hypothalamus In Feeding Behaviormentioning
confidence: 99%